Adding omega-3 fatty acids to a protein-based supplement during pre-season training results in reduced muscle soreness and the better maintenance of explosive power in professional Rugby Union players - Black, K. E.; Witard, O.C.; Baker, D.; Healey, P.; Lewis, V.; Tavares, F.; Christensen, S.; Pease, T.; Smith, B. (European Journal of Sport Science, 2018)
Evidence suggests that omega-3 fatty acid supplementation could reduce muscle soreness and maintain muscle function following eccentric exercise-induced muscle damage. The aim of this applied field study was to investigate the effectiveness of consuming a protein-based supplement containing 1546 mg of omega-3 polyunsaturated fatty acid (PUFA) (551 mg eicosapentaenoic acid (EPA) and 551 mg docosahexaenoic acid (DHA)) twice daily (FO) compared to a protein-based placebo (P) on muscle soreness, countermovement jump (CMJ) performance and psychological well-being in 20 professional Rugby Union players during 5 weeks of pre-season training. Players completed a 5-point-Likert soreness scale with 5 indicating "no soreness" and a questionnaire assessing fatigue, sleep, stress and mood each morning of training, plus they performed CMJ tests once or twice per week. Data were analysed using magnitude-based inferential statistics and are presented as percent beneficial/trivial/harmful. On day 35, there was a likely (% beneficial/trivial/harmful: 94/5/1) moderate (0.75, standardized mean difference (SMD)) beneficial effect of FO vs. P on the change in lower body muscle soreness compared with day 0 (FO: -3.8 ± 21.7%; P: -19.4 ± 11.2%). There was a likely (92/7/0) moderate (SMD: 0.60) beneficial effect of FO vs. P on CMJ performance (change from baseline to day 35, FO: +4.6 ± 5.9%; P: -3.4 ± 8.6%). From day 20, a moderate beneficial effect of FO on fatigue was observed. In terms of practical relevance, the moderate beneficial effect of adding fish oil to a protein-based supplement on muscle soreness translated into the better maintenance of explosive power in elite Rugby Union players during pre-season training.